Reading the South African transition - Manganyi, Chabani (PINS-Psychology in Society, 2024)
Maré, Gerhard (2014) Declassified: Moving beyond the dead end of race in South Africa. Auckland Park (Johannesburg): Jacana. ISBN 978-1-4314-2020-9 pbk. Pages 200. One of the most important temptations whilst reading an interesting and important text for the first time is imagining other ways in which the narrative could have been weaved together. Yet in a review, signals of outstanding themes and narrative brilliance such as those which I was happy to encounter in Gerhard Maré’s, Declassified: Moving beyond the dead end of race in South Africa, are always a welcome reward in the course of a review such as the present one. This is my second review of an important book after several decades. Consequently, I am mindful of the fact that I should not play at reimagining a version of a text conceived and written by someone else. Undoubtedly, given the range and complexity of Maré’s text, I would circumstances permitting, have preferred a second opportunity to study the text once more.